Recent Advances in Enzyme‐Based Biomaterials Toward Diabetic Wound Healing. Issue 2 (23rd December 2022) - Wang, Qi; Luo, Zheng; Wu, Yun-Long; Li, Zibiao
Abstract : Diabetic wound, also known as diabetic foot ulcer (DFU), is a form of chronic lesion that disrupts the patient's lifestyle and, in severe cases, may be fatal. Recent endeavors utilizing enzymes, particularly nanozymes in conjunction with other materials, have revealed the potential to treat diabetic wounds. Herein, the rational structural design of enzyme‐based biomaterials is summarized after presenting the types and processes of enzymes employed in diabetic wound healing, with the goal of better understanding the interaction between enzymes and other biological materials. The importance of enzyme catalytic activity, coupled with new therapeutic treatment strategies, is emphasized in the use of enzyme‐based biomaterials for diabetic wound healing. This review represents the most recent development in enzyme‐based biomaterials innovation for diabetic wound healing applications, and it can be used as a reference to guide other regenerative biomedicines from nanoenzyme biomaterials. Abstract : Enzyme‐based biomaterials have great potential in the treatment of diabetic wounds. This review summarizes the types and mechanisms of enzymes currently used in wound healing therapy, focusing on the structural design of enzyme‐based biomaterials and their various application strategies in diabetic wound treatment.